Abrasion process between a fibre mooring line and a corroded steel element during the transit and commissioning of a marine renewable energy device. (February 2016) - Herduin, Manuel; Banfield, Stephen; Weller, Sam D.; Thies, Philipp R.; Johanning, Lars
A bstract: The interaction between fibre rope and steel parts on vessels (fairlead and roller) is technically well understood but not commonly published in codes or practised by mariners. What appears to be a smooth steel surface to the naked eye can still be abrasive medium to synthetic mooring components. There are very few reports of external rope abrasion tests in the literature. The surface finish at the contact between the rope and the steel guide can cause damage and consequently prematurely degrade the exposed yarns of the rope and thus reduces the overall load bearing capacity of the rope. The standard ISO 18692[1] recommends that prolonged cycling of a rope around rollers should be avoided, however it is specified that occasional bending and running over rollers are allowable. There are two guides to specify surface roughness. MEG 3[2] states that steel fairleads should be polished to Ra 10, but in practise this may be difficult to achieve or obtain with carbon steel. The US Navy guide also states that the surface of steel should have better than 125 μi or 3.2 Ra[3] . The study presented here discusses the bending of a synthetic rope around a roller during transportation. It relates the motion behaviour of the vessel to rope wear and provides a detailed numerical simulation correlated with post analysis of the rope after the failure. The investigations show that the roughness of the steel roller caused the abrasion of the rope which was exacerbated through the vessel dynamics, resulting in the rope having an estimated residual strength of 14% MBL before rupture. The experimental tests have established a linear relation between strength loss and surface roughness and it was observed that the abrasion mainly occurs in the early stages of load cycling. The presented work recommends the use of lubricated nylon instead of carbon steel rollers to limit abrasive rope wear. The paper also devises a methodology to carefully assess and quantify potential rope abrasion to ensure that the residual rope strength withstands the required load capacity. Highlights: A very small amount of surface roughness on the bearing item combined with rough sea conditions can initiate significant abrasion. The abrasion effect occurs at the beginning of the load cycles, after-which the steel surface is polished by the rope. The surface roughness of contacting steel elements should be less than Ra 10 to avoid causing significant damage to fibre ropes. The use of lubricated nylon or polished stainless steel roller when available to limit abrasive wear is recommended. A numerical model can predict the amplitude of the loading regimes experienced by the line for a given sea states.